ANALISIS EFEKTIVITAS IMPLEMENTASI SISTEM PEMBAYARAN DIGITAL QRIS (QUICK RESPONSE CODE INDONESIAN STANDARD) DALAM MENINGKATKAN PENJUALAN USAHA MIKRO DAN KECIL DI KOTA PARIAMAN - Ilham Saputra Nanda; Jon Kenedi (Adisam Publisher, 2025)
This research aim of this research is to analyze the effectiveness of the implementation of the QRIS digital payment system in increasing their business sales. This is a field study employing a descriptive qualitative research method. The subjects of this research are micro and small business actors in the city of Pariaman, specifically in the district of Central Pariaman. Data collection techniques in this research include observation, interviews, and documentation.